Religious Values and Conflict of Laws (Stato, Chiese e pluralismo confessionale, 2016)
Paper, peer reviewed, for: Liber amicorum Tito Ballarino, Institut Suisse Droit Comparé.SUMMARY: 1. Preliminary Remarks - 2. Religious values and nationality - 3.Electio iuris and religious values - 4. Public policy and religious values - 5. The Conventional approach - 6. Conclusive Remarks.Abstract: The wide evolution of private international law is currently recalling attention to the general aspects of the discipline. Europeanization and globalisation of sources of private international law do not preclude the chance that conflict of laws should also deal with individual identities. To the extent that the European systems have hitherto offered to the application of foreign laws, we are faced with the problem of survival in Europe of an idea of the personality of laws. In fact it’s generally accepted that conflict of laws faces the individual identities of people involved in international relations. Cultural identity may be considered collective and individual at the same time, because each member of the group has an identity of its own. Religious values ontribute to defining the cultural identity of individuals: be it in Europe or other countries, cultures, values, civilization, religion, are never absent from the solutions of personal status. Stepping back from the analysis of some cases where religious values are relevant, this Article aims at a theoretical analysis of the subject, involving the contrast between value pluralism, conflict of laws and fundamental rights.